Quantifying apple diversity: A phenomic characterization of Canada's Apple Biodiversity Collection. Issue 6 (23rd June 2021) - Watts, Sophie; Migicovsky, Zoë; McClure, Kendra A.; Yu, Cindy H. J.; Amyotte, Beatrice; Baker, Thomas; Bowlby, David; Burgher‐MacLellan, Karen; Butler, Laura; Donald, Richard; Fan, Lihua; Fillmore, Sherry; et al.
Societal Impact Statement: A future with a secure and safe food supply requires humanity to preserve and exploit the vast variation available across agricultural plant species. Apples are one of the most widely consumed fruits and provide significant nutritional value worldwide. Here, we characterize key agricultural traits in a diverse collection of apples to provide a foundation for future apple improvement. We show that commercially successful apple varieties capture only a small fraction of apple diversity, and demonstrate that significant improvement is possible by tapping into existing genetic diversity. Summary: ● Here we present a comprehensive evaluation of apple diversity through phenotyping of Canada's Apple Biodiversity Collection (ABC) which contains over 1000 apple accessions. ● We assessed, over a 4‐year period, more than 20, 000 individual apples and quantified variation across 39 phenotypes, including phenology and fruit quality both at harvest and after 3 months of cold storage. ● We observe that apples in the ABC display a wide range of phenotypic variation that may prove useful for future apple improvement. For example, apples can differ by nearly 61‐fold in weight, 18‐fold in acidity, and 100‐fold in phenolic content. We quantified the dramatic changes to apple physiology that occur during 3 months of cold storage: on average, apples lost 39% of their firmness, 31% of their acidity, and 9% of their weight, but gained 7% in soluble solids. Harvest date, flowering date, and time to ripen were all positively correlated with firmness, which suggests that the developmental pathways that drive phenological events throughout the growing season may play a role in determining an apple's texture. Finally, we show that apple breeding has selected for a significant decline in phenolic content over the past 200 years: apple cultivars released after 1940 had a 30% lower median phenolic content than cultivars released before 1940. ● The data and analyses presented here not only provide a comprehensive quantification of the range across, and relationships among diverse apple phenotypes, but they also enable genetic mapping studies that will provide the foundation for future apple improvement via genomics‐assisted breeding. Abstract : A future with a secure and safe food supply requires humanity to preserve and exploit the vast variation available across agricultural plant species. Apples are one of the most widely consumed fruits and provide significant nutritional value worldwide. Here, we characterize key agricultural traits in a diverse collection of apples to provide a foundation for future apple improvement. We show that commercially successful apple varieties capture only a small fraction of apple diversity, and demonstrate that significant improvement is possible by tapping into existing genetic diversity.